Potensi Dan Efektivitas Pemungutan Bea Perolehan Hak Atas Tanah dan Bangunan (BPHTB) dalam Rangka Peningkatan Pendapatan Asli Daerah (PAD) Kota Banjarmasin - Hanum Krisna Sari; Dewi Rahayu (PPJP ULM, 2020)
This research aims to determine the potential and effectiveness, barriers, and strategiesin the BPHTB tax collection and the projection of BPHTB tax Banjarmasin City for theupcoming five years. This research uses quantitative descriptive research methods. Thedata types used are primary and secondary data, with data collection techniquesthrough interviews and documentation. The results showed that BPHTB taxBanjarmasin city is a local tax with an acceptable tax condition in raising the city ofBanjarmasin. BPHTB tax effectiveness rate in Banjarmasin City during 2014-2018 hasbeen excellent, with an average percentage of 104%. However, based on interviews,there are still some obstacles in BPHTB's tax due to invalid data, unfaithful taxpayers,lack of experts, and the local government's strategy to mitigate it by adding fieldofficers system and updating data, and tightening supervision. The five-year projectionthat will be growth is always showing positive developments by 24%.